From field to sky: measurement and modeling of transgenic switchgrass pollen dispersal in the atmosphere - Manu Nimmala; Hope A. Gruszewski; Regina Hanlon; Landon Bilyeu; Tyler Newton; Jessica Stockdale; Reginald J. Millwood; Charles Neal Stewart; Craig W. Powers; Shane D. Ross; Hosein Foroutan; David G. Schmale III (Environmental Monitoring and Assessment, 2026)
Accurate tracking and measurement of pollen dispersal in the atmosphere are essential for assessing cross-pollination risks, particularly in the case of genetically engineered (GE) crops. We conducted a series of unique release-recapture field studies with GE switchgrass in Oliver Springs, TN, USA. Two hundred transgenic switchgrass plants ( Panicum virgatum L. “Performer”) were planted at the center of a clear-cut field, with one block of 100 plants expressing orange fluorescent protein (OFP) under a switchgrass ubiquitin promoter (PvUBI1) and another block of 100 plants expressing OFP driven by a maize pollen-specific promoter (Zm13). Pollen was sampled from the atmosphere using fixed (ground-based) and mobile (drone-based) sampling devices at different distances from the source field, with Lagrangian stochastic dispersal simulations run for sampling periods using high-resolution wind measurements. The pollen emission rate was estimated by combining simulated and measured pollen concentrations, and strong diurnal trends were observed. Diurnal emission rate trends were positively correlated with wind speed, temperature, and vapor pressure deficit, while negatively correlated with relative humidity. In low-wind meandering conditions, incorporating changing wind direction into the dispersal modeling improved pollen emission rate estimation and model-measurement comparisons. This study assesses the effectiveness of high- and low-volume pollen samplers in relation to source strength up to 1 km from the source, enhancing understanding of pollen measurement techniques. Additionally, it is a proof-of-concept for drone-based pollen sampling and GMO pollen tracking using fluorescence measurements. Results from our experiments have significant implications for cross-pollination risk assessment, prediction, and management of airborne allergens.

Systematic review of wild birds as reservoirs of antimicrobial resistance: Implications for roof-harvested rainwater safety - Mira Cooper-Beknazarova; Ben van den Akker; Barbara Drigo; Kirstin Ross; Harriet Whiley; Craig R. Williams (International Journal of Hygiene and Environmental Health, 2026)

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

Physiological and behavioural plasticity improves resilience to chronic hypoxia and warming in a dryland river fish - Zoe A. Ross; Jonathan Marshall; Andrea Prior; Craig E. Franklin; Matthew Hipsey; Rebecca L. Cramp (Science of The Total Environment, 2025)

Effects of Five Serial Apnoeas Prior to a Running Time Trial in Competitive Athletes - Matthew John Barlow; Catherine Ross; Remmie Cockrell; Morgan Rubie; Harry Cahill; Craig Robertson; Jamie French; Antonis Elia (Journal of Science in Sport and Exercise, 2025)
Purpose This study aimed to determine whether a series of repeated maximal voluntary apnoeas is effective in improving subsequent time trial performance in competitive level track and field athletes. Methods Seventeen competitive runners volunteered for this study and based on their preferred competitive distance they were placed either in the 200 m (5 male, 4 female) or 1000 m group (3 male, 5 female). On two separate occasions (≤ 7 days apart), the participants performed a running time-trial that was preceded either by: (i) a standardised warm up (WO) or (ii) a standardised warm up succeeded by five repeated maximal dry static apnoeas (WA). Splenic volume, haematology and cardiovascular parameters were monitor at rest, before and after each time-trial. Results WA resulted in a significantly faster performance (27.51 ± 3.49 s; P = 0.009) compared with WO (27.96 ± 3.34 s) in the 200 m group, whereas no differences were observed in the 1000 m group (WA, 211.10 ± 26.18 s; WO, 215.82 ± 25.13 s, P = 0.120). No differences were noted in splenic volume between WO and WA in either group ( P ≥ 0.081). Haemoglobin was significantly elevated after breath-holding in the 200 m (+ 7 g/dL, P = 0.041) but not 1000 m group. Conclusion This study demonstrates that five repeated maximal apnoeas are capable of significantly improving a 200 m but not a 1000 m time-trial performance in competitive track and field athletes.

Age and growth of the Pacific goliath grouper ( Epinephelus quinquefasciatus ), the largest bony reef fish of the Tropical Eastern Pacific - Carolina Chong‐Montenegro; Matthew T. Craig; Gustavo A. Castellanos‐Galindo; Brad Erisman; Peter G. Coulson; Uwe Krumme; Rodrigo Baos; Luis Zapata; Angel Vega; D. Ross Robertson (Journal of Fish Biology, 2025)
We examined the age and growth of the Pacific goliath grouper ( Epinephelus quinquefasciatus ) from 210 samples collected from the main fish markets in Panama and Colombia. Ages from otoliths ranged from young‐of‐the‐year to 13 years, predominantly between 1 and 4 years. The von Bertalanffy growth parameters were L∞ = 207 cm, k = 0.13 year −1 and t 0 = −1.87 years. Instantaneous mortality rates ( Z ) were estimated at 36% in Colombia (ages 2–11) and 26% in Panama (ages 2–13).

Heat-tolerant algal symbionts may prevent extirpation of the threatened elkhorn coral, Acropora palmata, in Florida during intensifying marine heatwaves - Richard F. Karp; Fabrizio Lepiz-Conejo; Shayle B. Matsuda; Bryce Corbett; Alexandra D. Wen; Joseph D. Unsworth; Martine D’Alessandro; Ken Nedimyer; Amelia Moura; Erinn M. Muller; Zachary Craig; Diego Lirman; et al. (Coral Reefs, 2025)
The elkhorn coral, Acropora palmata , was historically a major reef-building species in the Caribbean, but has suffered devastating declines in recent decades. Despite significant restoration efforts in Florida, the marine heatwave of 2023 caused severe bleaching and mortality to both wild and restored colonies. To understand the disastrous impacts, we evaluated the variation in heat tolerance among Florida’s A. palmata population prior to the event. In 2022, we used rapid acute heat stress assays to assess the thermal tolerance of 172 adult colonies (125 unique genets) from four nurseries. We found variation in thermal tolerance (4.17°C range in ED50) that was attributed to nursery location (17.2% of variation), genet (25.9%), and symbiont abundance (15.6%). Algal symbiont type, however, was the strongest predictor of thermal performance, with the few (n = 10) colonies hosting Durusdinium being, on average, 1.9°C more thermally tolerant than corals hosting Symbiodinium . This difference would have decreased the effective heat stress accumulation during the 2023 event by ~92%. Therefore, despite considerable variation in thermal tolerance among Florida’s elkhorn corals, hosting Durusdinium appears to be the most effective mechanism for surviving such extreme heat stress. These findings suggest that restoration strategies that focus on rearing sexually derived A. palmata recruits with Durusdinium , followed by outplanting to suitable environments, may improve survival during future heatwaves. Combined with efforts to introduce additional elkhorn diversity from populations outside Florida, these approaches may be the most effective interventions to promote the continued survival of Florida’s elkhorn corals in the face of rapid climate change.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Rapid 2D hydrodynamic flood modeling using deep learning surrogates - Francisco Haces-Garcia; Natalya Ross; Craig L. Glennie; Hanadi S. Rifai; Vedhus Hoskere; Nima Ekhtari (Journal of Hydrology, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Variable persistence of an iconic arboreal mammal through the Black Summer wildfires - Ross L. Goldingay; Rohan J. Bilney; Craig Dunne (Forest Ecology and Management, 2024)

Lactational transfer of sulforaphane-N-acetylcysteine in vivo and in human breast milk - Ross Shore; Jonathan Behlen; Dylan McBee; Keerthana Prayaga; Faith Haugen; Lenore Craig; Michael Shields; Toriq Mustapha; Navada Harvey; Natalie Johnson (Toxicology and Applied Pharmacology, 2024)

Hawaiian coral holobionts reveal algal and prokaryotic host specificity, intraspecific variability in bleaching resistance, and common interspecific microbial consortia modulating thermal stress responses - Laura Núñez-Pons; Ross Cunning; Craig E. Nelson; Anthony S. Amend; E. Maggie Sogin; Ruth Gates; Raphael Ritson-Williams (Science of The Total Environment, 2023)

Marine reserve use by a migratory coastal shark, Carcharias taurus - Ross G. Dwyer; Michaela Rathbone; Deborah L. Foote; Mike Bennett; Paul A. Butcher; Nicholas M. Otway; Brett M. Louden; Fabrice R.A. Jaine; Craig E. Franklin; Carley Kilpatrick (Biological Conservation, 2023)

Long-term tracking reveals a dynamic crocodylian social system - Cameron J. Baker; Céline H. Frère; Craig E. Franklin; Hamish A. Campbell; Terri R. Irwin; Ross G. Dwyer (Animal Behaviour, 2023)

Conditional alternative movement tactics in male crocodiles - Kaitlin E. Barham; Cameron J. Baker; Craig E. Franklin; Hamish A. Campbell; Celine H. Frére; Terri R. Irwin; Ross G. Dwyer (Behavioral Ecology and Sociobiology, 2023)
In species where conflict is costly, individuals adopt alternative movement tactics to minimise the risk of competitive interactions. Dominant males often maintain defined territories, while less competitive males may be forced to adopt alternative tactics to maximise fitness and reduce conflict. However, the extent to which males switch tactics according to current social or physiological status is poorly understood. Using implanted acoustic tags and a fixed array of tracking receivers, we investigated how the behaviour of 78 male estuarine crocodiles ( Crocodylus porosus ) shifted over an 11-year period in relation to ontogeny, body condition, and the extent of physical injuries. We discovered that male crocodiles sorted into three common movement classes, with 51% of males maintaining the same movement class across consecutive years (max = 9 years). Males > 4 m in total length maintained confined territories both within and across years and had the greatest extent of injuries and the highest condition score, indicative of territory holders. In contrast, smaller males sorted into high movement roamer or low movement site-philopatric tactics, where the tactic an individual adopted was less stable between years and did not correlate with condition or external injuries. Our study reveals the socio-biological mechanisms by which estuarine crocodiles coexist within a restricted habitat. Significance statement Identifying individual-level differences in movement helps us predict which individuals are more likely to be involved in human-wildlife interactions. However, studying long-term shifts in movement is challenging, as large datasets of co-occurring individuals tracked in their natural environment over multiple years are required. We tracked a population of 78 male estuarine crocodiles (1030–4687 mm total length) in a shared environment over 11 years and assessed how eight movement traits were linked to body size and physical condition. At the population level, males sorted into different movement tactics according to ontogeny, with large territorial males having better body condition yet a greater incidence of injury. However, 49% of males showed variability across years, suggesting that tactics were conditional relative to environmental variability and a male’s own status. Our study provides insights into the mechanisms and costs of movement tactics in wild crocodile populations.

Fog trends in India: Relationships to fog type and western disturbances - Daniel K. E. Smith; Stephen R. Dorling; Ian A. Renfrew; Andrew N. Ross; Craig Poku (International Journal of Climatology, 2023)
Fog is a major hazard in wintertime over India, particularly in the Indo‐Gangetic Plains, leading to significant impacts for transport and human health. Using 3‐hourly surface observations, from 69 sites across India, all fog and dense fog events between 2000 and 2020 are identified. For each event, the main fog formation mechanism is objectively categorized using a classification algorithm, distinguishing between radiation, advection, evaporation, precipitation or cloud‐base lowering fog types. In contrast to the findings of other international studies, radiation fog dominates as the most common fog type at the vast majority of locations in India, accounting for 68.1% of all fog events and 70.0% of dense fog events. Statistically significant positive trends are seen in the frequency of all fog events at Delhi, Lucknow and Patna, in the Indo‐Gangetic plains, between 1997/1998 and 2018/2019, dominated by comparable statistically significant positive trends in radiation fogs. Western disturbances (WD) are often linked to the formation of fog in India. Using a climatology of WDs, we show that 46.9% of radiation fog onsets in Delhi in December and January, the primary fog months, happened in conjunction with an active WD event. Conversely, only 32.3% of WDs during these same months coincided with the onset of a radiation fog event. WD‐related radiation fog events are shown to cluster into three distinct groups, with WD centres located to the northwest (51.4% of cases), southwest (13.3%) and east (35.2%) of Delhi. Each cluster is shown to have coherent and distinct near‐surface characteristics which are conducive to fog formation. Trends in WD frequency cannot fully account for the observed trends in fog events. We argue that the fog trends are more likely the result of a complex interaction between urban expansion and the associated rapid change in aerosol loading, resulting in impacts on radiation balance, microphysics and heat‐island processes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Temperature‐mediated acquisition of rare heterologous symbionts promotes survival of coral larvae under ocean warming - Shayle B. Matsuda; Leela J. Chakravarti; Ross Cunning; Ariana S. Huffmyer; Craig E. Nelson; Ruth D. Gates; Madeleine J. H. van Oppen (Global Change Biology, 2022)
Reef‐building corals form nutritional symbioses with endosymbiotic dinoflagellates (Symbiodiniaceae), a relationship that facilitates the ecological success of coral reefs. These symbionts are mostly acquired anew each generation from the environment during early life stages (“horizontal transmission”). Symbiodiniaceae species exhibit trait variation that directly impacts the health and performance of the coral host under ocean warming. Here, we test the capacity for larvae of a horizontally transmitting coral, Acropora tenuis , to establish symbioses with Symbiodiniaceae species in four genera that have varying thermal thresholds (the common symbiont genera, Cladocopium and Durusdinium , and the less common Fugacium and Gerakladium ). Over a 2‐week period in January 2018, a series of both no‐choice and four‐way choice experiments were conducted at three temperatures (27, 30, and 31°C). Symbiont acquisition success and cell proliferation were measured in individual larvae. Larvae successfully acquired and maintained symbionts of all four genera in no‐choice experiments, and >80% of larvae were infected with at least three genera when offered a four‐way choice. Unexpectedly, Gerakladium symbionts increased in dominance over time, and at high temperatures outcompeted Durusdinium , which is regarded as thermally tolerant. Although Fugacium displayed the highest thermal tolerance in culture and reached similar cell densities to the other three symbionts at 31°C, it remained a background symbiont in choice experiments, suggesting host preference for other symbiont species. Larval survivorship at 1 week was highest in larvae associated with Gerakladium and Fugacium symbionts at 27 and 30°C, however at 31°C, mortality was similar for all treatments. We hypothesize that symbionts that are currently rare in corals (e.g., Gerakladium ) may become more common and widespread in early life stages under climate warming. Uptake of such symbionts may function as a survival strategy in the wild, and has implications for reef restoration practices that use sexually produced coral stock.

Opening Doors to Training Medical Toxicology Fellows from All Residency Backgrounds - Louise Kao; Michele Burns; Christine Murphy; Evan Schwarz; Steve Aks; Kavita Babu; Gillian Beauchamp; Rana Biary; Michele Burns; Nathan Charlton; Cathleen Clancy; Jonathan Ford; et al. (Journal of Medical Toxicology, 2022)

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Exploring good cycling cities using multivariate statistics - Andrew J. Collins; Craig A. Jordan; R. Michael Robinson; Caitlin Cornelius; Ross Gore (Environment Systems and Decisions, 2020)

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Characterization of a thermally tolerant Orbicella faveolata reef in Abaco, The Bahamas - Katherine E. Parker; Jeremy O. Ward; Erin M. Eggleston; Evan Fedorov; John Everett Parkinson; Craig P. Dahlgren; Ross Cunning (Coral Reefs, 2020)

Using individual‐based movement information to identify spatial conservation priorities for mobile species - Ross G. Dwyer; Hamish A. Campbell; Richard D. Pillans; Matthew E. Watts; Barry J. Lyon; Siddeswara M. Guru; Minh N. Dinh; Hugh P. Possingham; Craig E. Franklin (Conservation Biology, 2019)
The optimal design of reserve networks and fisheries closures depends on species occurrence information and knowledge of how anthropogenic impacts interact with the species concerned. However, challenges in surveying mobile and cryptic species over adequate spatial and temporal scales can mask the importance of particular habitats, leading to uncertainty about which areas to protect to optimize conservation efforts. We investigated how telemetry‐derived locations can help guide the scale and timing of fisheries closures with the aim of reducing threatened species bycatch. Forty juvenile speartooth sharks ( Glyphis glyphis ) were monitored over 22 months with implanted acoustic transmitters and an array of hydrophone receivers. Using the decision‐support tool Marxan, we formulated a permanent fisheries closure that prioritized areas used more frequently by tagged sharks and considered areas perceived as having high value to fisheries. To explore how the size of the permanent closure compared with an alternative set of time‐area closures (i.e., where different areas were closed to fishing at different times of year), we used a cluster analysis to group months that had similar arrangements of selected planning units (informed by shark movements during that month) into 2 time‐area closures. Sharks were consistent in their timing and direction of migratory movements, but the number of tagged sharks made a big difference in the placement of the permanent closure; 30 individuals were needed to capture behavioral heterogeneity. The dry‐season (May–January) and wet‐season (February–April) time‐area closures opened 20% and 25% more planning units to fishing, respectively, compared with the permanent closure with boundaries fixed in space and time. Our results show that telemetry has the potential to inform and improve spatial management of mobile species and that the temporal component of tracking data can be incorporated into prioritizations to reduce possible impacts of spatial closures on established fisheries.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Ontogenetic shifts in the nesting behaviour of female crocodiles - Cameron J. Baker; Craig E. Franklin; Hamish A. Campbell; Terri R. Irwin; Ross G. Dwyer (Oecologia, 2019)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Improving biocontrol of black vine weevil (Otiorhynchus sulcatus) with entomopathogenic fungi in growing media by incorporating spent mushroom compost - Ralph Noble; Andreja Dobrovin-Pennington; Jean Fitzgerald; Katie Dew; Craig Wilson; Kyle Ross; Colin Perkins (BioControl, 2018)

Singlicate Ligand Binding Assay Using an Automated Microfluidic System: a Clinical Case Study - Hao Jiang; Alex Kozhich; Jennifer Cummings; Janice Gambardella; Frank Zambito; Craig Titsch; Jonathan Haulenbeek; Kelli Phillips; Ross Fergus; Heather Myler (The AAPS Journal, 2017)

Identifying critical habitat for freshwater turtles: integrating long-term monitoring tools to enhance conservation and management - Mariana A. Micheli-Campbell; Marilyn J. Connell; Ross G. Dwyer; Craig E. Franklin; Brian Fry; Mark J. Kennard; Juan Tao; Hamish A. Campbell (Biodiversity and Conservation, 2017)

Recognition and Knowledge of Medications with Black Box Warnings Among Pediatricians and Emergency Physicians - Craig Geoffrey Smollin; Jonathan Fu; Ross Levin (Journal of Medical Toxicology, 2016)

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism - Alexandra C. G. Thomson; Paul H. York; Timothy M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2015)

Estimating dispersal distance in the deep sea: challenges and applications to marine reserves - Ana HilÃ¡rio; Anna Metaxas; Sylvie M. Gaudron; Kerry L. Howell; Annie Mercier; NÃ©lia C. Mestre; Rebecca E. Ross; Andreas M. Thurnherr; Craig Young (Frontiers in Marine Science, 2015)

No detectable impact of small-scale disturbances on ‘blue carbon’ within seagrass beds - Peter I. Macreadie; Paul H. York; Craig D. H. Sherman; Michael J. Keough; D. Jeff Ross; Aurora M. Ricart; Timothy M. Smith (Marine Biology, 2014)

The dynamics of potassium uptake and use, leaf gas exchange and root growth throughout plant phenological development and its effects on seed yield in wheat (Triticum aestivum) on a low-K sandy soil - Qifu Ma; Craig Scanlan; Richard Bell; Ross Brennan (Plant and Soil, 2013)

Microsatellite primer development for the seagrass Zostera nigricaulis (Zosteraceae) - Timothy M. Smith; Paul H. York; Annalise M. Stanley; Peter I. Macreadie; Michael J. Keough; D. Jeff Ross; Craig D. H. Sherman (Conservation Genetics Resources, 2013)

Observations of below-ground characteristics of young redwood trees (Sequoia sempervirens) from two sites in New Zealand – implications for erosion control - Christopher J. Phillips; Michael Marden; Suzanne Lambie; Alex Watson; Craig Ross; Scott Fraser (Plant and Soil, 2013)

C-Terminal trans-activation sub-region of VP16 is uniquely required for forskolin-induced herpes simplex virus type 1 reactivation from quiescently infected-PC12 cells but not for replication in neuronally differentiated-PC12 cells - Robert J. Danaher; Ross K. Cook; Chunmei Wang; Steven J. Triezenberg; Robert J. Jacob; Craig S. Miller (Journal of NeuroVirology, 2013)

Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Effects of Scleral Stiffness Properties on Optic Nerve Head Biomechanics - Armin Eilaghi; John G. Flanagan; Craig A. Simmons; C. Ross Ethier (Annals of Biomedical Engineering, 2010)

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

Rapid responses of vegetation to hydrological changes in Taylor Slough, Everglades National Park, Florida, USA - Thomas V. Armentano; Jay P. Sah; Michael S. Ross; David T. Jones; Hillary C. Cooley; Craig S. Smith (Hydrobiologia, 2006)

Phylogeography of the flag cabrilla Epinephelus labriformis (Serranidae): implications for the biogeography of the Tropical Eastern Pacific and the early stages of speciation in a marine shore fish - Matthew T. Craig; Philip A. Hastings; Daniel J. Pondella; D. Ross Robertson; Jorge A. Rosales‐Casián (Journal of Biogeography, 2006)
Aim To examine the role of previously described biogeographical boundaries in shaping phylogeographical relationships within and among two putative eastern Pacific sibling species, the flag cabrilla, Epinephelus labriformis and the Clipperton grouper, Epinephelus clippertonensis (Serranidae). Location Tropical Eastern Pacific (TEP). Methods Sequence data from the mitochondrial cytochrome b gene were obtained from samples throughout the range of the species. Coalescence analysis, mismatch distributions and an analysis of molecular variance ( amova ) were used to infer population differentiation. Results Overall, 49 haplotypes were found among 304 specimens, and there was significant structure corresponding to geographical locality ( amova , Φ ct = 0.198, P st = 0.207, P F st = 0.169, P F ct = 0.151, P = 0.036). Coalescence analysis indicates a population expansion at Clipperton Atoll during the mid‐Pleistocene. Main conclusions Our results suggest that previously described barriers to dispersal along the mainland of the TEP may not impinge on the dispersal ability of marine species, such as these groupers, that have long‐lived pelagic larvae. In contrast, gene flow between mainland and island populations of the readily distinguishable morphospecies E. labriformis and E. clippertonensis is restricted. The low level of genetic differentiation between the two species indicates that changes in external colour patterns may evolve more rapidly than genetic markers commonly used to delimit species boundaries. Thus a combination of colour differences and a lack of reciprocal monophyly may act as good indicators of incipient speciation in the marine environment.

Genetic management of the red squirrel, Sciurus vulgaris: a practical approach to regional conservation - Rob Ogden; Craig Shuttleworth; Ross McEwing; Silvana Cesarini (Conservation Genetics, 2006)

Recent invasion of the tropical Atlantic by an Indo‐Pacific coral reef fish - LUIZ A. ROCHA; D. ROSS ROBERTSON; CLAUDIA R. ROCHA; JAMES L. VAN TASSELL; MATTHEW T. CRAIG; BRIAN W. BOWEN (Molecular Ecology, 2005)
The last tropical connection between Atlantic and Indian–Pacific habitats closed c . 2 million years ago (Ma), with the onset of cold‐water upwelling off southwestern Africa. Yet comparative morphology indicates more recent connections in several taxa, including reef‐associated gobies (genus Gnatholepis ). Coalescence and phylogenetic analyses of mtDNA cytochrome b sequences demonstrate that Gnatholepis invaded the Atlantic during an interglacial period ∼145 000 years ago ( d = 0.0054), colonizing from the Indian Ocean to the western Atlantic, and subsequently to the central (∼100 000 years ago) and eastern Atlantic (∼30 000 years ago). Census data show a contemporary range expansion in the northeastern Atlantic linked to global warming.

Geologic and geochemical study of the Picacho gold mine, California: gold in a low-angle normal fault environment - Steven Losh; Dan Purvance; Ross Sherlock; E. Craig Jowett (Mineralium Deposita, 2005)

Assessing the ecological impacts of an introduced seastar: the importance of multiple methods - D. Jeff Ross; Craig R. Johnson; Chad L. Hewitt (Biological Invasions, 2003)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)